Penggunaan Sosial Media Dalam Meningkatkan Kecerdasan Santri (Digital Smart) Pada Pondok Pesantren Almansyuriyah - Tri Santoso; Sulistianto Sw; Ardian Dwi Praba; Syahriani (CV. Multi Kreasi Media, 2023)
The development of information and communication technology in this era has experienced a shift to digital transformation which is changing the industrial landscape. Previously, in the Industry 4.0 era, technology was only positioned as an information search engine. Now in the Social Era 5.0, technology and its functions are emphasized as part of human life. In its growth, many social networks have been manipulated for certain purposes, such as spreading false information or what is commonly known as hoaxes. It is important to emphasize that the role of Millennials today is to be smart in disseminating relevant information. Because in reality they are the ones who dominate the majority of social networking users in Indonesia. One of the social networking users who are among the millennials themselves are students in Islamic boarding schools. Therefore, in this millennial era, students must always be observant, intelligent and wise in using social media, whether in disseminating information in the form of positive content. Apart from that, students must be able to become active participants and active outreach on social media both in spreading da'wah and not be easily provoked or taken advantage of.